Editorial : Model organisms in plant science : Maize - Butron, Ana; Santiago, Rogelio; Gowda, Manje (Frontiers Media, 2023)
Maize has been an organism of historical importance to all biologists as eminent researchers such as Beadle, Emerson, McClintock, Stadler and Rhoades made ground-breaking genetic discoveries in maize that hold true for all living organisms (Andorf et al., 2016). Nowadays, plant lignocellulose represents the world’s greatest repository of renewable energy amenable to conversion into liquid, and maize has become one of the preferred choices due to their high biomass yields, broad geographic adaptation, carbon sequestration potential and nutrient utilization (Courtial et al., 2013; van der Weijde et al.). Therefore, this Research Topic aimed (1) to put forward the importance of research focuses in maize as a model organism, presenting recent developments and important accomplishments in moving forward the study of plants, and (2) to shed light on the progress made in the past decade working with maize as an important crop used worldwide.